Answer:
- f(t) = 6000*1.03^t
- k = 0.0295588
Explanation:
The formula for exponential growth can be written a couple of different ways. One I prefer uses the problem numbers directly:
population = (initial population) × (growth factor)^t
Here, the initial population is 6000, and the growth factor is 1+3% = 1.03. Then the function can be written as ...
f(t) = 6000·1.03^t
__
Another way to write the function is using the form ...
f(t) = (initial population) × e^(kt)
where k is the natural logarithm of the growth factor. In this form, we have ...
k = ln(1.03)
k ≈ 0.0295588
so the function would be written ...
f(t) = 6000·e^(0.0295588t)